ANALISIS KEBUTUHAN PENDIDIKAN MASYARAKAT - Amin Yusuf (Jurnal Penelitian Pendidikan, 2014)
Based on a belief that in order to assist in community development with appropriate education, the need for a research study that examined a variety of community needs for education and solutions. On the belief, the research with the above title aims to: (1) analyze the various needs education is urgent, and immediate solution can be resolved by the people in the village Kandri and (2) implementing affirmative action, mentoring programs and management of village libraries learning model for functional literacy tutors as a solution. Participatory methods or PRA, with the tools bervariatif data collectors, such as in-depth interviews, brainstorming, patisipatif observation, and documentation is a method used in the study. The results showed that, the library management assistance programs and rural development model functional literacy learning is an effective solution of many aspects that have been identified. The program can improve quality and expand access to coverage of services of non-formal education, and increase community participation in education development.